Creditor’s Right to Information in Corporate Bankruptcy Proceedings - Jokubauskas, Remigijus (Teisė, 2019)
This article examines the practical problems deriving from the exercise of the creditor’s right to information regarding the course of corporate bankruptcy proceedings. The legal regulation of foreign states shows that creditors shall participate in bankruptcy proceedings actively. Namely, timely information about the corporate bankruptcy proceedings allows creditors to exercise other rights and impact the decision-making in this process. Disputes often arise regarding how creditors can use this right to information and what legitimate restrictions can be established for its implementation.